The Application of Ilahiyah and Insaniyah Values in Microteaching Learning towards Professional Teachers - Abduldayev, Yerkhan; Mokhtar, Marzni Mohamed (Khalifa Journal of Islamic Education, 2024)
Education is a strategic effort to shape individuals with moral, spiritual, and professional character. In this context, the internalization of ilahiyah and insaniyah values is a key factor in the learning process, especially in microteaching courses. This study aims to examine the implementation of divine and human values in microteaching to shape prospective professional teachers with character. This study employs a descriptive qualitative method with a content analysis approach. Data were collected through observation and document analysis. The results indicate that the integration of ilahiyah and insaniyah values in microteaching is achieved through various strategies, such as providing real-life examples, crisis reflection, and reinforcing the value of honesty in teaching practices. The internalization of these values has been proven to enhance spiritual awareness, empathy, and the ability to educate students among prospective teachers. Thus, value-based microteaching not only enhances professional competence but also shapes teachers with noble character and moral responsibility toward students.